Upaya percepatan program pencegahan stunting dengan pendekatan pembinaan kader di Kota Medan - Fennisyah Andriani Saragih; Fitriani Pramita Gurning (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Stunting is a global problem that affects human development. Stunting, a nutritional health problem, has impacted and spread throughout the country, especially in Indonesia. The trend and target of reducing stunting have progressed but not significantly. Of course, there are still several contributing factors; therefore, specific efforts are needed to accelerate the reduction of stunting.Objectives: This study aimed to determine accelerated program efforts in stunting prevention using a cadre coaching approach in Medan City.Methods: This study uses a mixed methods approach that uses a sequential exploratory design through qualitative and quantitative analyses. The research was conducted on April 05, 2023, in Belawan Sicanang, Belawan Bahari, and Pekan Labuhan Villages. The sample taken by the researchers included 35 cadres. Data collection techniques used questionnaires with cadres who used a range scale. The statistical test for quantitative analysis used the univariate test to determine the description of cadre coaching on the running of the stunting program.Results: The results of the data taken directly by the researcher through a questionnaire instrument based on the Medan Mayor's Regulation (PERWAL) on Stunting Prevention Configuration in Medan City found that from the indicators of accelerating stunting prevention with a cadre coaching approach in Medan City, there were still cadres who had not participated in training on health promotion efforts related to stunting (25 %) and those who had participated in training (75 %).Conclusion: There is a relationship between cadre training and health promotion in reducing stunting.